Unveiling the needs for ethnoscience-based e-worksheets to enhance nature of science and environmental awareness of elementary school students - Wulan Octi Pratiwi; Sunyono Sunyono; Fatkhur Rohman; Rangga Firdaus (Indonesian Journal of Science and Mathematics Education)
This study aims to describe the analysis of the development needs of an ethnosciences-based e-worksheet. The research utilizes the 4D Research and Development model, specifically focusing on the define stage, which employs descriptive data analysis techniques. The research instruments consist of interviews with natural and social sciences teachers and questionnaires assessing the needs of both teachers and students. A preliminary study involved 136 students and 5 natural and social sciences teachers from 5 Elementary Schools in Bandar Lampung. The teachers' needs questionnaire results indicate that 100% of the teachers have not yet integrated natural and social sciences learning by connecting science knowledge with local Lampung culture. Similarly, the student's needs questionnaire shows that 89% have not experienced natural and social sciences learning integrated with Lampung's local culture. Furthermore, based on the results of the students' and teachers' needs questionnaires, 84% of the students answered "yes," indicating they strongly agree, and 100% of the teachers also answered "yes," indicating strong agreement, regarding the potential development of ethnosciences-based e-worksheet. This study implies the importance of instructional materials integrating local wisdom to enrich the learning process, support scientific literacy, and enhance environmental awareness.